Implementation Of Medan Mayor Regulation Number 18 Of 2021 On The Delegation Of Partial Waste Management Authority To Sub-District Heads Within The Medan City Government In Medan Helvetia Sub-District - Syahrazad; Syafruddin Ritonga; Adam (Faculty of Law, Universitas Pekalongan, 2024)
Medan Mayor Regulation Number 18 of 2021 provides a legal basis for delegating partial waste management authority to sub-district heads within the Medan City Government. The purpose of this regulation is to enhance the effectiveness of waste management at the sub-district level by empowering sub-districts as waste managers who are closer to the community. The implementation of this regulation in Medan Helvetia Sub-District faces various supporting and inhibiting factors. The supporting factors identified include the proximity between the sub-district and the community, participatory programs involving the community in cleanliness activities, and close coordination between the village heads and the sub-district administration. Participatory programs such as communal work (gotong royong) and waste management education have proven effective in raising public awareness about the importance of environmental cleanliness. However, several challenges hinder the implementation of this policy, including overlapping responsibilities between the sub-district and the Medan City Environmental Agency, budget and facility constraints, and the lack of an effective coordination mechanism among stakeholders. To overcome these obstacles, it is necessary to improve coordination between the sub-district and the Environmental Agency, develop more innovative cleanliness programs, and optimize existing resources. Additionally, active community participation is crucial to ensuring the successful implementation of this policy. By optimizing all involved elements, the implementation of Medan Mayor Regulation Number 18 of 2021 in Medan Helvetia Sub-District is expected to create a cleaner and healthier environment and serve as a model for other sub-districts in Medan City.